ANALISIS KEBERHASILAN PENGEMBANGAN PROYEK PROPERTI KOMERSIAL BANGUNAN CAMPURAN - Astana, I Nyoman Yudha; Dharmayanti, G. A.P. Candra; Delaranto, Vava Bensa (JURNAL SPEKTRAN, 2019)
ANALYSIS OF SUCCESSFUL PROJECT DEVELOPMENT OF MIXED-USE COMMERCIAL PROPERTY   ABSTRACT Property industry in Indonesia has contributed 9.4% againts national Brutto Domestic Product during 2016, and property industry growth in 2017 is predicted raise up to 15% from previous year with total capitalization in amount of 318 trillion rupiahs. Property companies have often run their property project without proper strategy and planning, and this circumstance causes property project failure in achieving the initial goal. That occured situation will have serious implication concerning to company reputation, budget, project neighbour, urban planning, possibility of criminal around project site, and tax revenue target. The objective of this research is to identify factors that affecting the succesful project development of mixed-use commercial property, and how the affects are. Respondents are the experts who worked at public listed property companies that registered in Indonesia Stock Exchange, for Property and Real Estate sub-sector, at period of 2016 – 2018. This research have two stages, first to reduce initial confirmatory indicators based on previous references by using Factor Analysis model, and second to analize whether reduced indicators could affect the successful project development of mixed-use commercial property by using Partial Least Square model. The result of analysis shows that the affecting factors are: X1 (Product Diversity and Permits), X2 (Feasibility Study), X3 (Funding and Construction Supervise), X4 (Product Quality and Operational Management), X5 (Design), X6 (Ease of Execution), X7 (Marketing Strategy) and X8 (Location and Building Maintenance). Correlation amongst variable shown by equation model Y = 0.167 X1 + 0.219 X2 + 0.196 X3 + 0.155 X6 + 0.226 X7 + 0.204 X8. However the factors that have positive and significant effect are: X7 (significant value 3.501), X8 (significant value 2.912), X6 (significant value 2.430), X2 (significant value 2.427), X3 (significant value 2.282) and X1 (significant value 2.083).